Use of Optional Exercises in Mathematics in Primary Classes - Shabatova Rabiģa Janasbay-kizi (International Journal on Integrated Education, 2022)
This article discusses the use of optional activities in the elementary grades to help students master topics in mathematics lessons, develop their interest in mathematics, and identify their talents.